THE MAINTENANCE OF WHITE SHRIMP (Litopenaeus vannamei) WITH DIFFERENT PERCENTAGE OF FEED - Edward Nababan; Iskandar Putra; Rusliadi ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on 18th March to 23rd April 2015 atBrackishwater Aquaculture Development Center Jepara, Central of Java. The aimof this research is to determine the optimum percentage of feed in shrimpsenlargement activity. The Completely Randomized Design was applied in thisresearch with one factor and three replication. Treatment consist of feed pellets; P1(15% from biomass/day), P2 (25% from biomass/day), P3 (35% frombiomass/day), P4 (45% from biomass/day) and P5 (55% from biomass/day). Awhite shrimp (Litopenaeus vannamei) in length of 1,62 cm and body weight of0,05 g were reared in bucket (15 unit) with 120L capacity and density of 100tail/bucket. During experiment, the shrimps were fed on pellets four times daily.The results showed that the different percentage of feed gave effect for whiteshrimp growth. The best percentage of feed is 25% from biomass/day (P2) wasoptimum and gave the total weight with 0,934 g, total length 4,042 cm, specificgrowth rate 9,76%, and survival rate with 95,33%.Keywords : Litopenaeus vannamei, percentage of feed, growth rate